PENGEMBANGAN LKPD ELEKTRONIK PELAJARAN MATEMATIKA SMP BERBASIS PEMBELAJARAN DISCOVERY LEARNING - Sumargiyani, Sumargiyani; Hasanah, Uswatun (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
The aim of this research is to produce an electronic LKPD that is suitable for use as material on a two-variable linear equation system (SPLDV) whose assessment is based on validity and practicality.  Development research with stages using the ADDIE model. This research used random sampling and a sample of class VIII-C SMP Muhammadiyah 6 Yogyakarta was obtained as many as 28 students.  There are three instruments used, namely material expert instruments, media expert instruments and student instruments. Data analysis techniques use qualitative and quantitative data analysis. Qualitative data analysis is to carry out theoretical studies and observations, while quantitative data analysis is to calculate material expert validation scores, media expert validation and student response questionnaires.  To assess the validity of the electronic LKPD, two material experts and two media experts were carried out, and to see the practicality of the students' responses.  From the results of the questionnaire distributed, the results of the electronic LKPD were very valid, from the material expert assessment with a score of 87.92% and the media expert's assessment with a score of 87.92%. The practicality of electronic LKPD in the practical category is based on responses in small class trials of 73.56% and large class 65.51%. The results of the research show that the electronic LKPD developed to be suitable for use for learning SPLDV material is based on the results of student responses with practical criteria and the results of expert assessment of the material and electronic LKPD media are very valid.